Patrimonialisation du biome de las Caatinga : imaginaires paysagers en changement dans le semi-aride brésilien - Caio Augusto Amorim Maciel (VertigO)
The caatinga biome presents a typical landscape of the dry hinterland of northeastern Brazil, constituting a region called sertão, where a tropical semiarid climate predominates. It features varied scenery, especially due to the low rainfall average, which is poorly distributed in the space. Despite its great biodiversity and its singular character, the caatinga has been stigmatized at the national geographic imaginary as an inhospitable environment, almost like a desert. This happened probably because of its rude and desiccated vegetal landscape - especially when compared to the Amazonian dense and lush rain forest. In consequence, its recognition as a natural area capable of cultural appreciation and protection was therefore delayed, leaving the caatinga off the list of biomes worthy of being classified as National Treasures by the Brazilian Constitution of 1988. Then, at the turn of the century, a number of social movements set forth through the debates about climate change, desertification and sustainable development, have led the Brazilian society to an impressive change on this kind of misrepresentation. However, the promotion of sustainability and conservation of the caatinga biome remains rather difficult, depending on many deep rooted cultural processes of appropriation and production of meanings by different actors involved in the revaluation of a very large natural patrimony (more than 900.000km2), also marked in history by an adverse imagery. Thus, the article aims to identify the new values and landscape representations that allow the caatinga to become a geographic object (both natural and cultural) worthy of being transmitted to future generations, insisting on the criteria of patrimonialization once it has been officially registered as a biosphere reserve, considering the example of the state of Pernambuco.